MANUSIA DAN TUJUAN PENCIPTAANNYA MENURUT PANDANGAN ISLAM - Yuliatun, Sholikah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2024)
Humans are the most perfect creatures compared to other creatures, because humans are equipped with reason to think, to create new knowledge, where this knowledge becomes a tool and container for humans in this life. Humans have the potential for goodness and progress for themselves and towards others. This study tries to show the extent of the position and priority of humans on this earth in Islamic philosophy. This research uses a literary review with data from published scientific journal references. The results of this literature research show that God has given humans senses and reason, which are human qualities, and it is humanity's obligation to maintain and develop these abilities